2016
DOI: 10.1371/journal.pone.0167202
|View full text |Cite
|
Sign up to set email alerts
|

Rare Variants in NOD1 Associated with Carotid Bifurcation Intima-Media Thickness in Dominican Republic Families

Abstract: Cardiovascular disorders including ischemic stroke (IS) and myocardial infarction (MI) are heritable; however, few replicated loci have been identified. One strategy to identify loci influencing these complex disorders is to study subclinical phenotypes, such as carotid bifurcation intima-media thickness (bIMT). We have previously shown bIMT to be heritable and found evidence for linkage and association with common variants on chromosome 7p for bIMT. In this study, we aimed to characterize contributions of rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, care must be taken to translate results from experimental mouse studies on atherosclerosis to patients. However, a genome-wide association study has already shown that a rare variant of NOD1 is associated with intima-media thickness in patients [11] suggesting a potential role for the NOD pathway in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, care must be taken to translate results from experimental mouse studies on atherosclerosis to patients. However, a genome-wide association study has already shown that a rare variant of NOD1 is associated with intima-media thickness in patients [11] suggesting a potential role for the NOD pathway in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…98 Some studies report the association between oligomerization domain-containing protein 1 genotypes and susceptibility to cerebrovascular diseases. 99 However, these links between SNPs and cerebrovascular diseases are controversial for different ethnicities, implying that combination of microbiome and genome-wide association studies, called “mGWAS,” is essential to unravel the complexity of cerebrovascular diseases. 100…”
Section: Future Directionsmentioning
confidence: 99%
“…A total of 34 families with a family-specific LOD score >0.1 at one of the four QTLs for plaque located at chromosomes 7q36, 11p15, 14q32 and 15q23, were selected for our current study; 12 families were sequenced as part of our discovery analyses and 22 families were genotyped on the Exome Array for our replication analyses. Details of the family selection have been published previously [ 12 ]. Additional replication analyses were performed using an independent sample of 556 unrelated Dominicans from NOMAS.…”
Section: Methodsmentioning
confidence: 99%